Game of Stars : Kiranmali and the Kingdom Beyond #2 - DasGupta, Sayantani; To, Vivienne (New York : Scholastic Press, 2019)
Months after Kiranmala's adventure in the Kingdom Beyond, a vision of the Demon Queen starts showing up in her bedroom, trying to tell Kiran something, but getting cutoff before she can finish; then she starts seeing an advertisement for an archery contest on her family's interdimensional television and Kiran realizes that she must return to her place of birth--where society is falling apart, a reality show is taking over, her friends are in danger, and she, once again, becomes the warrior princess she was meant to be.
Keywords: East Indian Americans -- Juvenile fiction; Princesses -- Juvenile fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy; East Indian Americans -- Fiction; Princesses -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Adventure fiction; Fantasy fiction